2014
DOI: 10.1002/cctc.201402134
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Efficient Platinum Catalyst Derived from a Semiconducting, DMF Solvate: Structural, Spectroscopic, Electrochemical, and Catalytic Characterization

Abstract: The reaction of [(NH3)4Pt](NO3)2 with LiTCNQF4 (TCNQF4=2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane) in dimethylformamide gives the product [(NH3)4Pt](TCNQF4)2⋅(DMF)4 (1). Subtle changes in the solvent conditions, however, result in a different product, [(NH3)4Pt](TCNQF4)2⋅Et2O⋅(CH3OH)4/3 (2). Both 1 and 2 have been characterized by X‐ray crystallography, vibrational (FTIR, Raman) and UV/vis spectroscopy, thermogravimetric analysis and electrochemistry. Single crystals of 1 indicate the presence of 3 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 38 publications
3
31
0
1
Order By: Relevance
“…The mid-point potentials are E m1 = À0.17 mV and E m2 = 0.524 mV (vs. Ag/Ag + ), in which E m is the average of the reduction (E p red )a nd oxidation (E p ox )p eak potentials andr epresents ac lose approximation of the reversible formal potential, E 0 f .T he separation in the potentials for the two processes is 541 mV,a nd is consistentw ith data reported in the literature under similar conditions. [24] These voltammetric data imply that, upon dissolution of 1 in DMF,T CNQF 4 2À and Mn 2 + are formed. In this scan range,n o other higher oxidations pecies are observed( e.g.,Mn 3 + ).…”
Section: [Mn 2 (Tcnqf 4 ) 2 (Dmf) 4 ]·3 Dmf (3)mentioning
confidence: 93%
See 3 more Smart Citations
“…The mid-point potentials are E m1 = À0.17 mV and E m2 = 0.524 mV (vs. Ag/Ag + ), in which E m is the average of the reduction (E p red )a nd oxidation (E p ox )p eak potentials andr epresents ac lose approximation of the reversible formal potential, E 0 f .T he separation in the potentials for the two processes is 541 mV,a nd is consistentw ith data reported in the literature under similar conditions. [24] These voltammetric data imply that, upon dissolution of 1 in DMF,T CNQF 4 2À and Mn 2 + are formed. In this scan range,n o other higher oxidations pecies are observed( e.g.,Mn 3 + ).…”
Section: [Mn 2 (Tcnqf 4 ) 2 (Dmf) 4 ]·3 Dmf (3)mentioning
confidence: 93%
“…O'Mullane et al used films derived from MTCNQ or MTCNQF 4 (M=Cu + , Ag + )t oc atalyset he otherwise very slow redox reactiono ff erricyanidea nd thiosulfate ions in aqueous solution, [21] and, more recently,B ond and co-workersd iscovered that blue crystalline [(NH 3 ) 4 Pt](TCNQF 4 ) 2 displayed super-catalytic activity and reusability,w ith respectt ot he above reactionu nder the same conditions. [24] This encouraged us to explore whether the manganese-basedn etworks 1-3 werec apable of exhibiting similar catalytic behaviour with respectt ot his redox reaction. Unfortunately,n either 1 nor 2 were stable in aqueous solution containing K 3 [Fe(CN) 6 ]a nd Na 2 S 2 O 3 .B yc ontrast, compound 3 was stable in water and was employeda saheterogeneous catalystfor the reactionindicated in Equation (3).…”
Section: Formation Of [Mn 2 (Tcnqf 4 ) 2 (Dmf) 4 ](5) In Aqueous Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…[6a] Martin et al [13] also demonstrated that [(NH 3 ) 4 4À ions to complete the reaction. The overall reaction scheme is illustrated in Figure 4.…”
mentioning
confidence: 99%